Wychowanie dziecka jako wyraz ludzkiej tragedii - Dembiński, Mariusz (Studia Edukacyjne, 2019)
Raising, reduced to the formula of up-bringing does not (Polish: wy-chowan-nie), allows us to reveal what is hidden, and by denying it (-not), it enables a person to experience the sense of his essence and see the tragedy of his upbringing and the sense of his life. Featured upbringing and up-bringing-does not (written separately) results from the difference in the approach to truth. Today, upbringing in its objectifying children truth refers to the concept of veritas, and because it lost its original meaning or aletheia, in search of the truth of upbringing, it was reduced to the formula of up-bringing-does not. With the help of this formula, an attempt was made to reveal the real sense of upbringing and the conditions that should be met in order for human up-bringing-does not to have a human (aletheia) dimension.